2014
DOI: 10.3141/2454-07
|View full text |Cite
|
Sign up to set email alerts
|

Charging Behavior Impacts on Electric Vehicle Miles Traveled

Abstract: The growing market for plug-in electric vehicles (PEVs) features new models of battery electric vehicles (BEVs) and plug-in hybrid electric vehicles (PHEVs) with varying battery sizes and electric driving ranges. How are the various models being used in the real world? A common assumption in PEV impact analysis is that PEV owners will maximize their vehicle's utility by appropriately sizing the battery to their driving needs and by charging their vehicle as much as possible to recover the cost of the vehicle p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 74 publications
(41 citation statements)
references
References 6 publications
0
41
0
Order By: Relevance
“…Single digit percentages (around 5%) of charging events occur at these locations. However, these charging events can still be important for longer journeys and can be perceived as a safety net for other charging options (Dong et al, 2014;Morrissey et al, 2016;Nicholas et al, 2017a;Plötz and Funke, 2017;Tal et al, 2014). These locations are used more frequently by BEVs compared to PHEVs.…”
Section: Charge Point Activity and Locationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Single digit percentages (around 5%) of charging events occur at these locations. However, these charging events can still be important for longer journeys and can be perceived as a safety net for other charging options (Dong et al, 2014;Morrissey et al, 2016;Nicholas et al, 2017a;Plötz and Funke, 2017;Tal et al, 2014). These locations are used more frequently by BEVs compared to PHEVs.…”
Section: Charge Point Activity and Locationsmentioning
confidence: 99%
“…One final issue associated with PEV charging was first identified by Tal et al (2013). Their analysis of GPS tracked PEVs in California found that some adopters of PHEVs do not plug-in their vehicles at all.…”
Section: Charge Point Activity and Locationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Rauh et al [18] used the same data and reported that the actual use of an EV can reduce the desired range. Tal et al [19] analyzed the travel data of 3,500 plug-in hybrid EVs and showed that a vehicle with a larger battery tends to be charged away from home and used for longer distances. Greaves et al [14] analyzed the driving data for 166 vehicles and concluded that an EV with a range as low as 60 km and a charging station at home can accommodate well over 90% of day-to-day driving.…”
Section: Driving Data Analysismentioning
confidence: 99%
“…It has been shown [41] that most people who currently drive EVs charge up at home or at work, where they know charging will be available. The Department of Energy has a current Workplace Charging Challenge [42] to encourage this growth.…”
Section: Policies For Electric Vehiclesmentioning
confidence: 99%